The Impact Of The Arabic Language On The Integration Of Religious and Human Sciences: A Reading On The Perspectives Of Jurists And Linguists/ أثر اللغة العربية في التكامل بين العلوم الشرعية والإنسانية قراءة في رؤية الفقهاء واللغويين - Abuzaid, Wasfy Ashour (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The need for integration in religious sciences reaches the level of necessity in the humanities sciences. As for the integration between religious sciences and humanities, the need for it is necessary due to the returns and benefits it brings to both fields. The intended goals of each field can only be achieved at an individual level through integration. Similarly, the intended purposes of both major areas can only be achieved through integration between them in terms of influence, activation, engagement, and exchange. The Arabic language, learning, and teaching are significant guarantees for fostering this integration. This is due to the essential role of the Arabic language in dealing with religious sciences and its unique ability to provide a common thread between Islamic sciences on the one hand and other related fields on the other hand. Hence, the importance of teaching the Arabic language becomes evident. The Arabic language has become the point of convergence and pivot for all human sciences, underscoring its significance in fostering integration among these disciplines. If Arabic has a significant role in facilitating integration among religious sciences, it has assumed paramount importance in shaping this integration among the human sciences. The results and their discussion: A vital conclusion has been reached by reviewing the statements of scholars and linguists regarding the significance of Arabic for understanding Islamic sciences and by citing the opinions of language experts and their modern branches. This conclusion is that the Arabic language has become the universal bridge for both religious sciences and human sciences. This will become evident through the research.